2015
DOI: 10.1007/s11816-015-0351-x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Arabidopsis WRI1 enhanced seed mass and storage oil content in Camelina sativa

Abstract: Vegetable oils are essential for human and animal diets and have been used for industrial applications such as cosmetics and lubricants. Camelina sativa, which contains 35-45 % storage oils of seed dry weight, is an emerging oilseed crop. In addition, Arabidopsis WRINKLED1 (AtWRI1) is known to be an AP2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 64 publications
3
54
0
1
Order By: Relevance
“…This is in accordance with the study where B. napus WRI1 was overexpressed in Arabidopsis , leading to seed oil content increases of 10–40% (Liu et al, 2010) and the study by An and Suh (2015) mentioned above.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in accordance with the study where B. napus WRI1 was overexpressed in Arabidopsis , leading to seed oil content increases of 10–40% (Liu et al, 2010) and the study by An and Suh (2015) mentioned above.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that overexpression of the AtWRI1, AtHb2 , and BvHb2 gene could increase the oil content up to 29.9, 20.2, and 25.9%, respectively in field cress. A similar increase has been demonstrated in camelina, where a seed-specific overexpression of AtWRI1 yielded a 14% increase in total seed oil content (An and Suh, 2015). An even higher increase has been shown in maize where ZmWRI1 -overexpression generated an average increase in seed oil content of 30.6% (Shen et al, 2010).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…WRINKLED1 (WRI1) was shown to be an essential transcription factor for TAG synthesis in many species, and its overexpression led to 10-30% increase in seed oil content in arabidopsis, rapeseed and even maize (Cernac and Benning, 2004;Baud et al, 2007;Liu et al, 2010;Pouvreau et al, 2011;Wu et al, 2014). Overexpression of arabidopsis AtWRI1 in camelina seeds led to an increase in seed weight and seed size, and as expected, to 8-31% increase in seed oil content (An and Suh, 2015). Although camelina already has three copies of endogenous WRI1, it is remarkable that significant yield gain could be achieved by overexpression of an orthologous gene.…”
Section: Improving Camelina Oil Yieldmentioning
confidence: 52%